Self-development through peer guidance for youth in Bandan Hurip Village in determining their careers - Nugraheni, Dian; Permana, Ghaza Fawwaz Ijlali; Rohimansyah, Rohimansyah (Jurnal Abmas, 2026)
The era of globalization, along with the lack of motivation and understanding among village youth in Laksana Mulya, Harapan Mulya, and Bandanpurwa hamlets regarding educational and career directions, is the main background for this community service. This Kuliah Kerja Nyata Berdampak (KKN-Berdampak) aims to provide insight, deepen adolescents' self-understanding, and equip them with basic skills in developing mature career plans. The implementation method uses a peer guidance approach that includes personal, social, learning, and career guidance. The implementation consists of three main stages: planning through observation, implementation through group discussions, and the creation of a "My Dream Map," and evaluation using Likert-scale pre-test and post-test instruments. This program involved 32 participants aged 13-18 years. The results of the community service showed a significant increase in understanding of self-potential and career plans. Participants' average understanding score increased in the post-test. In addition, the number of participants in the "very understanding" category increased. In conclusion, interventions through peer guidance have proven effective in facilitating peer support, increasing adolescents' self-confidence, and providing a strategic foundation for preparing for a more competitive future.
Keywords: community service; mentoring; peer guidance; self-potential; youth development